2019
DOI: 10.3390/app9030366
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Depressants and Collector Dosage in Fluorite Flotation Process Based on DoE Methodology

Abstract: Alternative processes have been proposed for selective separation of fluorite and gangue minerals (carbonates and silicates) present in fluorspar ores. Calcination and gravity separation processes are methods that have low efficiency and high cost. Flotation is a chemical process that becomes important when high ore grades are required; however, the selectivity is inhibited by the superficial similarity of the chemical composition of minerals. Accordingly, interactions between dissolved ionic species of fluori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The plot of grade and recovery versus pH showed that as the pH of pulp was increased from 7 to 10, both grade and recovery were increased but after that a slight decline in grade and recovery was noted. This indicates that around pH 10, the collector-mineral bond is much more stable leading to optimum recovery of 93.02% (Zhao et al 2012;Corpas-Martinez et al 2019). So, for the subsequent flotation trials, the pH of pulp was maintained at 10.…”
Section: Effect Of Ph Of the Pulpmentioning
confidence: 96%
“…The plot of grade and recovery versus pH showed that as the pH of pulp was increased from 7 to 10, both grade and recovery were increased but after that a slight decline in grade and recovery was noted. This indicates that around pH 10, the collector-mineral bond is much more stable leading to optimum recovery of 93.02% (Zhao et al 2012;Corpas-Martinez et al 2019). So, for the subsequent flotation trials, the pH of pulp was maintained at 10.…”
Section: Effect Of Ph Of the Pulpmentioning
confidence: 96%
“…A complete description of the cell is carried out in a previous work [30]. Oleic acid was used in all tests as a fluorite collector at a constant dosage of 400 g/t, based on a previous work [31].…”
Section: Cell Flotationmentioning
confidence: 99%
“…The order of adding the reagents was as follows: First, once the pH has been reached the value of 9.5, the QT depressant is added to the pulp and conditioned for 5 min [8]. Then the collector is added and let it condition for 2 more min.…”
Section: Mechanical Cell Flotationmentioning
confidence: 99%
“…Fluorite is commercialized according to its grade as acid grade fluorite (CaF 2 > 97%) and metallurgical grade (CaF 2 < 97%). To obtain acid grade fluorite it is necessary to use physic-chemical beneficiation methods such as froth flotation [7,8]. Froth flotation is based on surface reactions between minerals and chemical reagents such as collectors and depressant.…”
Section: Introductionmentioning
confidence: 99%